HUBUNGAN LINGKUNGAN FISIK RUMAH DAN PERILAKU MEROKOK DENGAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS SUKANAGALIH KABUPATEN CIANJUR - Dzahraini, Devina; Abdurrahmat, Asep Suryana; Yogaswara, Dadan (Jurnal Kesehatan Komunitas Indonesia, 2025)
Pneumonia is the leading cause of death from infection in children globally. The aim of this study was to analyze the relationship between the physical environment of the home and smoking behavior with the incidence of pneumonia in toddlers. The research method used was quantitative with a case-control study design. The case group consisted of 52 respondents and the control group consisted of 104 respondents (case-control ratio of 1:2). The independent variables in this study were housing density, ventilation area, humidity, and family members' smoking behavior, while the dependent variable was the incidence of pneumonia in infants. The case population in this study was infants aged 12–59 months who suffered from pneumonia in 2024, and the control population was all infants aged 12–59 months who did not suffer from pneumonia in 2024. The research instruments used were questionnaires, measurement sheets, hygrometers, and roll meters. The results of the bivariate test using the chi-square test showed that there was a significant relationship between housing density (p-value 0.001 with OR = 3.499), ventilation area (p-value 0.004 with OR = 2.895), humidity (p-value 0.047 with OR = 2.120), and family members' smoking behavior (p-value 0.015 with OR = 3.037) with the incidence of pneumonia in infants. The conclusion of this study is that there was a relationship between housing density, ventilation area, humidity, and family members' smoking habits with the incidence of pneumonia in infants. Recommendations for community health centers include the need to monitor the living conditions of the local community and conduct individual education regarding the dangers and health impacts of cigarette smoke.